PENGARUH KOMUNIKASI TERHADAP IMPLEMENTASI KEBIJAKAN AKTA KELAHIRAN DI DESA SUNGAI BESAR KECAMATAN MATAN HILIR SELATAN KABUPATEN KETAPANG - Hidayat E.42009026 (FISIP Universitas Tanjungpura Pontianak, 2013)
This script had aim to determine how much influence of communications towards implementation Of Birth Certificate In Sungai Besar Village South Matan Hilir district Ketapang Regency. This study based by expert’s theories then compared by the problem that happened at Sungai Besar Village South MatanHilir District Ketapang Regency. Communication is suspected as one of the factors that influence the implementation in the birth certificate at the Sungai Besar Village. This study use quantitative research methods. Based by questionnaires were distributed, get the data then processed using a computer program Statistical Product and Service Solutions (SPSS) V.19 to test the hypothesis. The Samples taken to a Head of family yet have birth certificates that as many as 71 people. The result of this study that found a significant difference between the communication of implementation in the birth certificate of Sungai Besar Village. Evidenced by the positive value of the correlation coefficient is equal to 0.611. The effect of Communication on policy implementation birth certificate in the village of Sungai Besar at 37,33%, while 62.67% are influenced by other factors outside the study. Keywords: communication, implementation, Policies, birth certificates.